Две судьбы: роман / Семен Малков - Малков Семен Наумович (Гелиос, 2003)
Экземпляры: К.Х. (20240416) / Инвентарный номер: 38857 / Цена: 76.01 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: М 19 / ББК: 84(2Рос=Рус)6